Cyclical Fluctuations in Strike Durations - Harrison, Alan; Stewart, Mark B. (American Economic Review, 1989)
Canadian data on strikes between 1946 and 1983 are used to estimate linear regression models for the logarithm of completed duration. A thorough investigation of the influence of the business cycle reveals strong support for the hypothesis that strike durations are countercyclical. The cyclical effect is shown to be robust to both the choice of cyclical variable and the econometric specification, and the magnitude of the effect is quite substantial. Experimentation with different representations of the cycle reveals that it is difficult to improve on a simple formulation involving a single continuous variable.